2020
DOI: 10.1111/jpn.13363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary amino acid levels and ambient temperature on mixed muscle protein turnover in Pectoralis major during finisher feeding period in two broiler lines

Abstract: Two broiler lines A and B were fed experimental diets from 21 to 42 days with an objective to determine Pectoralis major protein turnover (PT) as affected by the dietary amino acid (AA) levels and ambient temperature. Experimental diets (n = 9 replicate pens per diet) were formulated to 3,150 kcal/kg with five levels of digestible lysine (dLys) −80, 90, 100, 110 and 120% of recommended AA level giving g dlys/Mcal values of 2.53, 2.85, 3.17, 3.48 and 3.80 respectively. All other AA was formulated to a fixed rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
1
24
3
1
Order By: Relevance
“…A decreasing mixed muscle FSR with increasing age of the broiler was also found in present study for both strains. Interestingly, the FSR (%/D) in modern broilers as observed in the present study was higher than that of broilers reared in the past decades ( Jones et al., 1986 ; Tesseraud et al., 1996 ; Pym et al., 2004 ; Maharjan et al., 2020b ). The higher synthesis rates in current lines of broilers were accompanied by higher degradation rates as well.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…A decreasing mixed muscle FSR with increasing age of the broiler was also found in present study for both strains. Interestingly, the FSR (%/D) in modern broilers as observed in the present study was higher than that of broilers reared in the past decades ( Jones et al., 1986 ; Tesseraud et al., 1996 ; Pym et al., 2004 ; Maharjan et al., 2020b ). The higher synthesis rates in current lines of broilers were accompanied by higher degradation rates as well.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier studies that measured FSR in mixed muscle in pectoralis major in broilers over age found progressive and significant decrease in FSR values (22.4 to 12.5%/D) ( Tesseraud et al., 1996 ; Urdaneta-Rincon and Leeson, 2004 ; Maharjan et al., 2020b ). A decreasing mixed muscle FSR with increasing age of the broiler was also found in present study for both strains.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Protein accretion increased as dietary AA level increased as indicated by the increased 42 d breast and tenders meat yields and BC results ( Figure 4 , Table 5 , and Table 6 ). Protein turnover measurements in Pectoralis major were also conducted in the current trial where the results are reported in Maharjan et al. (2020b) .…”
Section: Discussionmentioning
confidence: 99%
“…There is reduced protein synthesis ( Maharjan et al., 2020b ) in heat-stressed broilers, because of downregulation of IGF1-mTOR pathway and changes in mRNA expression of AA transporters in intestine ( Habashy et al., 2017 ; Ma et al., 2018 ). Glucocorticoids such as corticosterone act as mediator of muscle protein catabolism, which tends to be elevated in heat-stressed broilers ( Soleimani et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%